A high-stiffness fully biodegradable material and its preparation method and application
By combining plant fiber pulp with polylactic acid fiber and adding wet stiffness enhancement particles, and after high-temperature hot pressing, a high-stress fully biodegradable material is prepared, which solves the problem of deterioration in the strength and stiffness of existing materials during freezing and heating, and achieves efficient decoration and durability for hot and cold beverages.
Patent Information
- Application Number
- CN202311486916.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-09
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2043-11-09
AI Technical Summary
The strength and stiffness of existing fast food packaging materials have deteriorated during freezing and heating, which cannot meet the requirements of filling hot and cold beverages and food, and at the same time has caused serious damage to the ecological environment.
Plant fiber pulp is used to combine with polylactic fibers, and wet stiffness enhancement particles (polycaprolactone and polyvinyl alcohol) are added. After high-temperature hot pressing, a high-stress fully biodegradable material is prepared.
After freezing and heating, the retention rate of breakage and stiffness of this material is greater than 90%. It can accommodate hot and cold beverages and food at the same time, and perform well under the heating conditions of aircraft meals.
Smart Images

Figure CN117777687B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of degradable environmentally friendly materials, and particularly relates to a high-stiffness fully biodegradable material and a preparation method and application thereof. Background Art
[0002] At present, fast food on trains, high-speed trains and airplanes is frozen and transported at low temperatures, and heated before eating. This requires that the fast food box material has good mechanical strength and stiffness after freezing and heating. Most of the existing fast food packaging is made of polypropylene, which is difficult to degrade. As its use increases, it will cause serious damage to the ecological environment.
[0003] Starch-based materials are used to replace some plastic materials to manufacture upgraded products of plastic tableware. Their performance is acceptable for ordinary tableware, but when they need to be stored at low temperatures (-18°C), the lunch boxes made of conventional starch-based materials will become hard and brittle after freezing, and are easily damaged during transportation. Moreover, after heating, the strength of the lunch boxes will decrease, and the feel of use will be poor.
[0004] Plant fiber is a widely used, low-cost, fully biodegradable material. However, the base paper of paper cups made of plant fiber pulp is coated with polyethylene on the surface for hot drinks and wax on the inner surface for cold drinks. It cannot hold both hot and cold drinks at the same time. When a cup for hot drinks is used to hold cold drinks, it will quickly absorb water and become soft in the air. This is because the food packaging material made of plant fiber pulp absorbs a lot of water during the thawing process, and its strength and stiffness deteriorate, which cannot meet the requirements of holding food.
[0005] Therefore, developing a completely biodegradable material that can simultaneously hold hot and cold beverages and foods and withstand freezing and heating has important significance and broad commercial prospects. Summary of the invention
[0006] The primary purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and to provide a method for preparing a high-stiffness fully biodegradable material.
[0007] Another object of the present invention is to provide a high-stiffness fully biodegradable material prepared by the method.
[0008] Another object of the present invention is to provide application of the high-stiffness fully biodegradable material.
[0009] The purpose of the present invention is achieved through the following technical solutions:
[0010] A method for preparing a high-stiffness fully biodegradable material comprises the following steps:
[0011] (1) adding wet stiffness enhancing particles to plant fiber pulp having a beating degree of 20°SR to 70°SR, and then sequentially adding a sizing agent and an oil-proofing agent, stirring and mixing evenly to obtain pretreated plant fiber pulp; wherein the wet stiffness enhancing particles are polycaprolactone and polyvinyl alcohol;
[0012] (2) The pretreated plant fiber pulp obtained in step (1) is stirred and mixed with polylactic acid fiber to be uniformly mixed, and then made into paper, and then subjected to high temperature hot pressing to obtain a high-stiffness fully biodegradable material.
[0013] The plant fiber pulp described in step (1) is at least one of bleached pulp of coniferous wood, broadleaved wood, bamboo or other types of plant fibers, or unbleached pulp of coniferous wood, broadleaved wood, bamboo or other types of plant fibers; preferably at least one of bleached coniferous wood pulp, unbleached coniferous wood pulp, bleached broadleaved wood pulp, unbleached broadleaved wood pulp, bleached bamboo pulp and unbleached bamboo pulp; more preferably bleached coniferous wood pulp.
[0014] The beating degree of the plant fiber pulp in step (1) is preferably 30°SR to 40°SR; more preferably 30°SR to 38°SR.
[0015] The weight average molecular weight (Mw) of the polycaprolactone described in step (1) is 20,000 to 100,000, preferably 80,000.
[0016] The polyvinyl alcohol described in step (1) is preferably 1799 polyvinyl alcohol (the model of the polyvinyl alcohol particles is 1799, i.e., the degree of polymerization is 1700 and the degree of alcoholysis is 99%); further preferably, it is 1799 polyvinyl alcohol particles with a particle size of 100 to 1200 mesh; more preferably, it is 1799 polyvinyl alcohol particles with a particle size of 300 to 1000 mesh.
[0017] The mass ratio of polycaprolactone to polyvinyl alcohol in the wet stiffness enhancing particles described in step (1) is (1:9) to (5:5); preferably (2:8) to (5:5); more preferably 2:8.
[0018] The amount of wet stiffness enhancing particles added in step (1) is 0.1-5% of the mass (absolute dry) of the plant fiber pulp; preferably 0.5-2% of the mass (absolute dry) of the plant fiber pulp.
[0019] The sizing agent described in step (1) is at least one of alkyl ketene dimer emulsion AKD and alkenyl succinic anhydride ASA; preferably alkyl ketene dimer emulsion AKD.
[0020] The amount of the sizing agent added in step (1) is 0.2-4.0% of the mass (absolute dry) of the plant fiber pulp; preferably 1.5-2% of the mass (absolute dry) of the plant fiber pulp.
[0021] The oil-proofing agent described in step (1) is an acrylate copolymer oil-proofing agent or the like.
[0022] The amount of the oil-proofing agent added in step (1) is 0.5-3% of the mass (absolute dry) of the plant fiber pulp; preferably 1-1.2% of the mass (absolute dry) of the plant fiber pulp.
[0023] In step (1), the order of adding the components is: wet strength enhancing particles, sizing agent and oil repellent (interval time is 20 to 50 minutes, preferably 20 to 30 minutes), that is, each time a component is added, it is stirred for 20 to 50 minutes (preferably 20 to 30 minutes) to ensure that it is fully mixed.
[0024] The polylactic acid fibers described in step (2) are polylactic acid chopped fibers, and the average length thereof is 2 mm to 8 mm (preferably 4 to 5 mm).
[0025] The mass ratio of the pretreated plant fiber pulp to the polylactic acid fiber in step (2) is (4:6) to (8:2); preferably (5:5) to (7:3).
[0026] The paper weight in step (2) is 40 to 500 g / m 2 ; preferably 120 to 160 g / m 2 .
[0027] The high temperature hot pressing described in step (2) is performed by using a soft roller calender, a common calender or other roller calenders commonly used in the papermaking industry to perform high temperature hot pressing, and the composite material is passed through the calender pressure zone to achieve a calendering effect.
[0028] The conditions of high temperature hot pressing described in step (2) are: calendering temperature 60-200°C, calendering line pressure 20-300 kN / m, and paper machine speed 100 m / min-1000 m / min; preferably: calendering temperature 160-180°C, calendering line pressure 100-120 kN / m, and paper machine speed 600 m / min.
[0029] A high-stiffness fully biodegradable material is prepared by any of the methods described above.
[0030] The high-stiffness fully biodegradable material is used in the preparation of paper cups, paper straws, food packaging materials, etc.
[0031] The paper cups include cold drink cups and hot drink cups. The material has good stiffness and bursting resistance when containing cold drinks and hot drinks, and can be used as cold drink cups and hot drink cups.
[0032] The food packaging materials include fast food packaging boxes and the like.
[0033] Compared with the prior art, the present invention has the following advantages and effects:
[0034] 1. The present invention provides a method for preparing a completely biodegradable material that can simultaneously hold hot and cold beverages and foods and can withstand freezing and heating: a certain amount of wet stiffness enhancing particles are sequentially added to the pulp after pulping, the mixture is stirred and mixed evenly, a sizing agent is added to the pulp, the mixture is stirred and mixed evenly, an oil-proofing agent is added, the mixture is stirred and mixed evenly, and the mixture is stored in a pulp storage tower for use; the pretreated pulp is mixed evenly with polylactic acid in a certain proportion, and then the mixture is made into paper by a paper machine; finally, the paper is subjected to high-temperature hot pressing inside or outside the machine to obtain a completely biodegradable food packaging material, and after the material is successively frozen, stored, and heated, the bursting resistance and stiffness retention rate of the material are greater than 90%.
[0035] 2. The present invention uses plant fiber pulp and polylactic acid as main raw materials, and adds wet stiffness enhancing particles (polycaprolactone + polyvinyl alcohol), which can synergistically improve the stiffness of the composite material, resist the loss of strength caused by condensed water after freezing, and also reduce the strength loss caused by freezing and heating.
[0036] 3. The high-stiffness fully biodegradable material prepared in the present invention can be used in the following scenarios: (1) It can have good stiffness when holding both cold drinks and hot drinks, and can be used as a cold drink cup or a hot drink cup; (2) It can still have excellent stiffness after being frozen and reheated with food, and can be used as a food packaging material and placed in a freezer together with food, and can be directly taken out and heated in an oven to meet the heating requirements of airplane meals; (3) It can be used to roll paper straws, which have higher stiffness than ordinary paper straws, and there is no problem of a significant decrease in stiffness after being soaked in liquid. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a physical picture of the composite material prepared in Example 1 of the present invention without post-freezing heating treatment.
[0038] Figure 2 This is a physical picture of the composite material prepared in Example 1 of the present invention after being frozen and then heated. DETAILED DESCRIPTION
[0039] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art. The test methods for which specific experimental conditions are not specified in the following examples are usually in accordance with conventional experimental conditions. Unless otherwise specified, the reagents and raw materials used in the present invention can be obtained commercially.
[0040] The bleached coniferous wood pulp involved in the embodiments and comparative examples of the present invention is of Stone brand, purchased from SMURFIT-STONE Contanier Co., Ltd.; the polylactic acid fiber was purchased from Zibo Baina New Material Technology Co., Ltd., with a specification of 5 mm×1.51D.
[0041] The sizing agent involved in the examples and comparative examples of the present invention is alkyl ketene dimer emulsion (AKD), purchased from Yueyang Antai Tairui Fine Chemicals, with implementation standard: Q / JBRG001-2009, solid content: ≥15%, pH value: 2-4.
[0042] The oil-proofing agent involved in the examples and comparative examples of the present invention is an acrylate copolymer oil-proofing agent purchased from Arkema (Changshu) Chemical Co., Ltd.
[0043] The wet stiffness enhancing particles involved in the embodiments of the present invention and the comparative examples are polycaprolactone and polyvinyl alcohol; wherein, polycaprolactone was purchased from Wuhan Haishan Technology Co., Ltd., with a weight average molecular weight of 80,000 Mw and a melting point of 60-62°C; the brand of polyvinyl alcohol is Wokai, purchased from Sinopharm Chemical Reagent Co., Ltd., with a degree of polymerization of 1700 and a degree of alcoholysis of 99%.
[0044] Example 1
[0045] A method for preparing a completely biodegradable material that can hold hot and cold beverages and foods and can withstand freezing and heating comprises the following steps:
[0046] (1) polycaprolactone (weight average molecular weight 80000) and 1799 polyvinyl alcohol particles with a particle size of 300 mesh were mixed in a ratio of 2:8 (polycaprolactone: polyvinyl alcohol = 2:8 (mass ratio)) to obtain wet stiffness enhanced particles; then the particles were added to bleached coniferous wood pulp with a beating degree of 30°SR in an amount of 0.5wt% (the absolute dry mass ratio of the wet stiffness enhanced particles to the bleached coniferous wood pulp with a beating degree of 30°SR), stirred for 30 minutes, and then 1.5wt% of sizing agent AKD (the absolute dry mass ratio of the sizing agent to the plant fiber) was added, stirred for 20 minutes, and finally 1wt% of acrylate copolymer oil-proofing agent (the absolute dry mass ratio of the oil-proofing agent to the plant fiber) was added, and stirred for 20 minutes to obtain pretreated plant fiber pulp;
[0047] (2) The pretreated plant fiber pulp and polylactic acid fiber were mixed in a ratio of 5:5 (absolute dry weight ratio), wherein the average length of the polylactic acid fiber was 5 mm, and after being stirred evenly, paper was made into paper using a papermaking machine, with a basis weight of 160 g / m 2 The dried paper was calendered by a soft roller calender at a temperature of 160°C and a calendering line pressure of 100 kN / m, and the paper machine speed was 600 m / min.
[0048] Example 2
[0049] A method for preparing a completely biodegradable material that can hold hot and cold beverages and foods and can withstand freezing and heating, comprising the following steps:
[0050] (1) polycaprolactone (weight average molecular weight 80000) and 1799 polyvinyl alcohol particles with a particle size of 500 mesh were mixed in a ratio of 3:7 (polycaprolactone: polyvinyl alcohol = 3:7 (mass ratio)) to obtain wet stiffness enhanced particles; then the particles were added to bleached coniferous wood pulp with a beating degree of 35°SR in an amount of 1wt% (absolute dry weight ratio of wet stiffness enhanced particles to bleached coniferous wood pulp with a beating degree of 35°SR), stirred for 30 minutes, and then 1.6wt% AKD (absolute dry weight ratio of sizing agent to plant fiber) was added, stirred for 20 minutes, and finally 1wt% acrylate copolymer oil-proofing agent (absolute dry weight ratio of oil-proofing agent to plant fiber) was added, stirred for 20 minutes, and pretreated plant fiber pulp was obtained;
[0051] (2) The pretreated plant fiber pulp and polylactic acid fiber were mixed in a ratio of 6:4 (absolute dry weight ratio), wherein the average length of the polylactic acid fiber was 5 mm, and the paper was made after being stirred evenly, with a basis weight of 160 g / m 2 The dried paper was calendered by a soft roller calender at a temperature of 170°C and a calendering line pressure of 110 kN / m, and the paper machine speed was 600 m / min.
[0052] Example 3
[0053] A method for preparing a completely biodegradable material that can hold hot and cold beverages and foods and can withstand freezing and heating, comprising the following steps:
[0054] (1) polycaprolactone (weight average molecular weight 80000) and 1799 polyvinyl alcohol particles with a particle size of 800 mesh were mixed in a ratio of 4:6 (polycaprolactone: polyvinyl alcohol = 4:6 (mass ratio)) to obtain wet stiffness enhanced particles; then the particles were added to bleached coniferous wood pulp with a beating degree of 38°SR in an amount of 1.5wt% (absolute dry weight ratio of wet stiffness enhanced particles to bleached coniferous wood pulp with a beating degree of 38°SR), stirred for 30 minutes, and then 2wt% AKD (absolute dry weight ratio of sizing agent to plant fiber) was added, stirred for 20 minutes, and finally 1.2wt% acrylate copolymer oil-proofing agent (absolute dry weight ratio of oil-proofing agent to plant fiber) was added, and stirred for 20 minutes to obtain pretreated plant fiber pulp;
[0055] (2) The pretreated plant fiber pulp and polylactic acid fiber were mixed in a ratio of 7:3 (absolute dry weight ratio), wherein the average length of the polylactic acid fiber was 5 mm, and the paper was made after being stirred evenly, with a basis weight of 160 g / m2 The dried paper was calendered by a soft roller calender at a temperature of 180°C and a calendering line pressure of 120 kN / m, and the paper machine speed was 600 m / min.
[0056] Example 4
[0057] A method for preparing a completely biodegradable material that can hold hot and cold beverages and foods and can withstand freezing and heating, comprising the following steps:
[0058] (1) polycaprolactone (weight average molecular weight 80000) and 1799 polyvinyl alcohol particles with a particle size of 1000 mesh were mixed in a ratio of 5:5 (polycaprolactone: polyvinyl alcohol = 5:5 (mass ratio)) to obtain wet stiffness enhanced particles; then the particles were added to bleached coniferous wood pulp with a beating degree of 35°SR in an amount of 2wt% (absolute dry weight ratio of wet stiffness enhanced particles to bleached coniferous wood pulp with a beating degree of 35°SR), stirred for 30 minutes, and then 1.8wt% AKD (absolute dry weight ratio of sizing agent to plant fiber) was added, stirred for 20 minutes, and finally 1.1wt% acrylate copolymer oil-proofing agent (absolute dry weight ratio of oil-proofing agent to plant fiber) was added, and stirred for 20 minutes to obtain pretreated plant fiber pulp;
[0059] (2) The pretreated plant fiber pulp and polylactic acid fiber were mixed in a ratio of 6:4 (absolute dry weight ratio), wherein the average length of the polylactic acid fiber was 4 mm, and the paper was made after being stirred evenly, with a basis weight of 120 g / m 2 The dried paper was calendered by a soft roller calender at a temperature of 170°C and a calendering line pressure of 100 kN / m, and the paper machine speed was 600 m / min.
[0060] Comparative Example 1
[0061] A method for producing a biodegradable packaging material comprises the following steps:
[0062] (1) adding polycaprolactone (weight average molecular weight 80000) to bleached coniferous wood pulp with a beating degree of 38°SR, the addition amount is 1.5wt% (absolute dry mass ratio of polycaprolactone strong particles to bleached coniferous wood pulp with a beating degree of 38°SR), stirring for 30 minutes, then adding 2% AKD (absolute dry mass ratio of sizing agent to plant fiber), stirring for 20 minutes, and then adding 1.2wt% acrylate copolymer oil-proofing agent (absolute dry mass ratio of oil-proofing agent to plant fiber), stirring for 20 minutes, to obtain pretreated plant fiber pulp;
[0063] (2) The pretreated plant fiber pulp and polylactic acid fiber were mixed in a ratio of 7:3 (absolute dry weight ratio), wherein the average length of the polylactic acid fiber was 5 mm, and the paper was made after being stirred evenly, with a basis weight of 160 g / m2 The dried paper was calendered by a soft roller calender at a temperature of 180°C and a calendering line pressure of 120 kN / m, and the paper machine speed was 600 m / min.
[0064] Comparative Example 2
[0065] A method for producing a biodegradable packaging material comprises the following steps:
[0066] (1) adding 1799 polyvinyl alcohol particles with a particle size of 800 mesh to bleached coniferous wood pulp with a beating degree of 38°SR, the addition amount is 1.5wt% (absolute dry mass ratio of polyvinyl alcohol particles to bleached coniferous wood pulp with a beating degree of 38°SR), stirring for 30 minutes, then adding 2wt% AKD (absolute dry mass ratio of sizing agent to plant fiber), stirring for 20 minutes, and then adding 1.2wt% acrylate copolymer oil-proofing agent (absolute dry mass ratio of oil-proofing agent to plant fiber), stirring for 20 minutes, to obtain pretreated plant fiber pulp;
[0067] (2) The pretreated plant fiber pulp and polylactic acid fiber were mixed in a ratio of 7:3 (absolute dry weight ratio), wherein the average length of the polylactic acid fiber was 5 mm, and the paper was made after being stirred evenly, with a basis weight of 160 g / m 2 The dried paper was calendered by a soft roller calender at a temperature of 180°C and a calendering line pressure of 120 kN / m, and the paper machine speed was 600 m / min.
[0068] Comparative Example 3
[0069] A method for producing a biodegradable packaging material comprises the following steps:
[0070] (1) polycaprolactone and 1799 polyvinyl alcohol particles with a particle size of 800 mesh were mixed in a ratio of 4:6 (polycaprolactone: polyvinyl alcohol = 4:6 (mass ratio)) to obtain wet stiffness enhanced particles; then the particles were added to bleached coniferous wood pulp with a beating degree of 38°SR in an amount of 1.5wt% (absolute dry weight ratio of wet stiffness enhanced particles to bleached coniferous wood pulp with a beating degree of 38°SR), stirred for 30 minutes, and then 1.2wt% of acrylate copolymer oil-proofing agent (absolute dry weight ratio of oil-proofing agent to plant fiber) was added, stirred for 20 minutes, and finally 2wt% of AKD (absolute dry weight ratio of sizing agent to plant fiber) was added, stirred for 20 minutes, and pretreated plant fiber pulp was obtained;
[0071] (2) The pretreated plant fiber pulp and polylactic acid fiber were mixed in a ratio of 7:3 (absolute dry weight ratio), wherein the average length of the polylactic acid fiber was 5 mm, and the paper was made after being stirred evenly, with a basis weight of 160 g / m 2The dried paper was calendered by a soft roller calender at a temperature of 180°C and a calendering line pressure of 120 kN / m, and the paper machine speed was 600 m / min.
[0072] Effect Example
[0073] The materials prepared in Examples 1 to 4 and Comparative Examples 1 to 3 were frozen and heated for testing, and the materials that were not frozen and heated were used as controls; wherein, the performance test method of the paper after freezing is as follows: the materials prepared in the examples and comparative examples are placed in a refrigerator (-18°C), taken out after 4 hours, and allowed to stand in the air for 15 minutes, and the bursting resistance and stiffness before and after freezing are tested according to GB / T 454-2020 "Determination of Burst Resistance of Paper" and GB / T 22364-2018 "Determination of Bending Stiffness of Paper and Paperboard"; the performance test method of the paper after freezing and heating is as follows: the materials prepared in the examples and comparative examples are placed in a refrigerator (-18°C), taken out after 4 hours, and then heated in an oven at 100°C for 15 minutes, allowed to stand in the air for 15 minutes, and the bursting resistance and stiffness are tested, and the test standards are the same as above.
[0074] The material prepared in Example 1 without freezing or heating is shown in the figure below: Figure 1 As shown, the material prepared in Example 1 after freezing and heating is shown in FIG. Figure 2 shown.
[0075] The test results of the materials prepared in Examples 1 to 4 and Comparative Examples 1 to 3 after freezing and heating are shown in Tables 1 and 2.
[0076] Table 1 Burst resistance index of composite materials (kPa·m 2 / g)
[0077] sample Before freezing After freezing After reheating from frozen Example 1 5.12 4.85 4.91 Example 2 4.98 4.68 4.81 Example 3 4.75 4.48 4.55 Example 4 4.62 4.43 4.51 Comparative Example 1 4.58 2.78 2.82 Comparative Example 2 4.67 2.95 3.17 Comparative Example 3 4.76 3.19 3.22
[0078] Table 2 Stiffness of composite materials (mN)
[0079] sample Before freezing After freezing After freezing and heating Example 1 197 180 185 Example 2 189 174 180 Example 3 182 168 173 Example 4 108 99 103 Comparative Example 1 90 58 60 Comparative Example 2 101 65 66 Comparative Example 3 105 70 72
[0080] It can be seen from the experimental data of Examples 1 to 4 that the materials prepared within the scope of the present invention, after being frozen and dried successively, have a small loss in strength of the composite material, can hold hot and cold beverages and foods, and can withstand freezing and heating conditions, and the retention rates of burst resistance and stiffness are both over 90%.
[0081] The present invention adopts a composite material prepared from plant fiber, polylactic acid and wet stiffness enhancing particles. The fully biodegradable material prepared by high-temperature hot pressing can greatly improve the stiffness of the composite material, resist the loss of strength caused by condensed water after freezing, and also reduce the strength loss caused by freezing and heating.
[0082] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a high-stiffness fully biodegradable material, characterized in that: The steps include: (1) adding wet stiffness enhancing particles to plant fiber pulp having a beating degree of 20°SR to 70°SR, then sequentially adding a sizing agent and an oil-proofing agent, stirring and mixing the mixture to obtain pretreated plant fiber pulp; The wet stiffness enhancing particles are polycaprolactone and polyvinyl alcohol; (2) mixing the pretreated plant fiber pulp obtained in step (1) and the polylactic acid fiber uniformly, and then forming paper, and then hot pressing at high temperature to obtain a high-stiffness fully biodegradable material; The mass ratio of polycaprolactone to polyvinyl alcohol in the wet stiffness enhancing particles described in step (1) is 2:8 to 5:5; The amount of wet stiffness enhancing particles added in step (1) is 0.5-2% of the mass of the plant fiber pulp; The conditions of high temperature hot pressing described in step (2) are: calendering temperature 60-200° C., calendering line pressure 20-300 kN / m, and paper machine speed 100 m / min-1000 m / min.
2. The method for preparing a high-stiffness fully biodegradable material according to claim 1, characterized in that: The weight average molecular weight of the polycaprolactone in step (1) is 20,000 to 100,000; The polyvinyl alcohol described in step (1) is 1799 polyvinyl alcohol; The mass ratio of the pretreated plant fiber pulp to the polylactic acid fiber described in step (2) is 4:6 to 8:
2.
3. The method for preparing a high-stiffness fully biodegradable material according to claim 2, characterized in that: The polyvinyl alcohol particle size described in step (1) is 1799 polyvinyl alcohol particles with a particle size of 100 to 1200 mesh; The mass ratio of the pretreated plant fiber pulp to the polylactic acid fiber described in step (2) is 5:5 to 7:
3.
4. The method for preparing a high-stiffness fully biodegradable material according to claim 1, characterized in that: The sizing agent described in step (1) is at least one of alkyl ketene dimer emulsion AKD and alkenyl succinic anhydride ASA; The amount of the sizing agent added in step (1) is 0.2-4.0% of the mass of the plant fiber pulp; The oil-proofing agent described in step (1) is an acrylate copolymer oil-proofing agent; The amount of the oil-proofing agent added in step (1) is 0.5-3% of the mass of the plant fiber pulp.
5. The method for preparing a high-stiffness fully biodegradable material according to claim 4, characterized in that: The sizing agent described in step (1) is alkyl ketene dimer emulsion AKD; The amount of the sizing agent added in step (1) is 1.5-2% of the mass of the plant fiber pulp; The amount of the oil-proofing agent added in step (1) is 1 to 1.2% of the mass of the plant fiber pulp.
6. The method for preparing a high-stiffness fully biodegradable material according to claim 1, characterized in that: The plant fiber pulp described in step (1) is at least one of bleached coniferous pulp, unbleached coniferous pulp, bleached broadleaf pulp, unbleached broadleaf pulp, bleached bamboo pulp and unbleached bamboo pulp; The beating degree of the plant fiber pulp in step (1) is 30°SR to 40°SR; The polylactic acid fibers described in step (2) are polylactic acid chopped fibers, and the average length thereof is 2 mm to 8 mm; The paper weight in step (2) is 40 to 500 g / m 2 .
7. A high stiffness fully biodegradable material, characterized by: It is prepared by the method according to any one of claims 1 to 6.
8. Use of the high-stiffness fully biodegradable material according to claim 7 in the preparation of paper cups, paper straws or food packaging materials.
9. The use according to claim 8, characterized in that: The paper cups include cold drink cups and hot drink cups; The food packaging material comprises a fast food packaging box.
Citation Information
Patent Citations
Completely biodegradable food packing material and preparation method thereof
CN102079820A
Preparation process of degradable packing box for fast food
CN103819753A